Compostos organoestânicos derivados do ácido valpróico: preparação, elucidação estrutural e estudo preliminar da atividade biológica in vitro - Bárbara Patrícia de Morais (2013)
The synthesis, characterization and structural authentication of organotin valproates, [{Me2SnVPA}2O]2 (1), [{Bu2SnVPA}2O]2 (2), [PhSn(O)VPA]6 (3), [Me3SnVPA]n (4), [Bu3SnVPA]n (5) and Ph3SnVPA (6) are described in this work. Moreover, preliminary studies of the biological activity of (1) - (6). have been performed. Chapter 1 comprises a short review concerning organotin carboxilates reported in the literature, discussing synthetic and the various structural arrangements of such complexes. In addition their potential biological activities are discussed. Chapter 2 details the main aspects of the biological activity of valproic acid, as well as the preparation of the sodium valproate.The preparation and structural characterization of the new organotinvalproates with diorganotin precursors, [{Me2SnVPA}2O]2 (1), [{Bu2SnVPA}2O]2 (2) and [PhSn(O)VPA]6 (3) are outlined in Chapter 3. Advanced spectroscopic techniques were employed in the characterization process of (1) - (3), such as: Infrared,1H, 13C and 119Sn-NMR in solution, solid state 119Sn-NMR, 119Sn Mössbauer spectroscopy. In addition the structures of complexes (1) and (3) have been determined by X-ray diffraction. Complex (1) displays a distannoxanic structure and a hexameric drum-like crystallographic arrangement was found for (3). Chapter 4 describes the synthesis and characterization of the new organotin valproates with triorganotin precursors [Me3SnVPA]n (4) and [Bu3SnVPA]n (5), and ofPh3SnVPA (6) recently reported in the literature. The same spectroscopic techniques used to characterize complexes (1) - (3) have been employed in authentication of (4) - (6) . A polymeric crystallographic motif was found for complex (4) in view of the X-ray crystallographic studies. Finally the preliminary results of microbiologic screening of complexes (1) - (6) are reported in Chapter 5. The tests were performed in the presence of the following microorganisms: (i) Gram-positive bacteria: Bacillus cereus (ATCC 11778), Listeria monocytogenes (ATCC15313), Staphylococcus aureus (ATCC29212), Streptococcus sanguinis (ATCC49456); (ii) Gram-negative bacteria: Escherichia coli (ATCC25922), Pseudomonas aeruginosa (ATCC27853) and Salmonella typhimurium (ATCC14028); (iii) yeasts: Candida albicans (ATCC 18804), Candida tropicalis (ATCC 750), Candida glabrata (ATCC 90030), Candida parapsilosis (ATCC 22019), Candida lusitaniae (CBS 6936) and Candida dubliniensis (Isolate 28). The results were expressed in terms of average percentage of inhibition and compared with the same results obtained for the valproic acid, sodium valproate and the organotin chlorides.